The Study of Drying Kinetics and Qualities of Dried Banana Slices by Vacuum-Infrared dryer - Im-erb, Natthapak; Witinantakit, Kittisak (Srinakharinwirot University Engineering Journal, 2021)
The objective of this research was to study of drying kinetics, specific energy consumption, color quality, water activity, develop empirical mathematical modeling, effective moisture diffusivity coefficient and activated energy for drying of banana slices by combined vacuum and infrared. An initial moisture content of banana slices was about 181-186% dry basis (d.b.). Drying processes were conducted by an absolute pressure at 10 kPa with drying temperature at 40, 50 and 60 oC, completely, final moisture content of banana slices was 10% d.b. The result shown that an increasing of temperature would affect to drying rate increased whereas drying time and specific energy consumption decreased. The final moisture content of banana slice was 7.2-10.54% d.b. and water activity was about 0.263-0.319. However, the changing in color of banana slices would not significantly different in L*, a* and b* values. Therefore, the drying of banana slices at absolute pressure of 10 kPa and drying temperature at 60 oC was the optimized condition for drying banana slices. Furthermore, the best equation for predicting of drying kinetics was a drying equation of Midilli with the highest decision coefficient (R2) at 0.99974, the lowest root mean square error (RMSE) was 0.00462 and the lowest chi-squared reduction ( ) was 2.432x10-05. Effective moisture diffusivity coefficients were between 6.85x10-11-14.03x10-11 m2/s and the activated energy was 31,160.83 kJ/mol.